Innate immune activation of NFκB and its antagonism by poxviruses - Bowie, Andrew; Brady, Gareth (My University, 2014)
In recent years there has been an acceleration of discovery in the field of innate anti-viral immunity to the point that many of the key events in early virus sensing and the discrete anti-viral responses they trigger have been elucidated in detail. In particular, pattern recognition receptors (PRRs) that detect viruses at the plasma membrane, in endosomes, and within the cytosol have been characterized. Upon stimulation by viruses, most of these PRRs trigger signal transduction pathways culminating in NFκB activation. NFκB contributes both to type I interferon induction, and to production of pro-inflammatory cytokines from infected cells. Our understanding of host anti-viral innate immunity has been greatly aided by an appreciation of the ways in which poxviruses have evolved strategies to inhibit both innate sensing and effector responses. A recurring feature of poxviral immunomodulation is the apparent necessity for poxviruses to evolve multiple, non-redundant inhibitors of NFκB activation which often appear to act on the same innate signalling pathway. The reason for such apparent over-targeting of one transcription factor is not clear. Here we describe the current understanding of how host cells sense poxvirus infection to trigger signalling pathways leading to NFκB activation and pro-inflammatory cytokine induction, and the ways in which poxviruses have evolved to concisely antagonize these systems.
PUBLISHED
Keywords: Poxvirus; NFκB; IL-1; TNF; Viral immune evasion